Perspectives on Exercise Intensity, Volume and Energy Expenditure in Habitual Cycle Commuting - Schantz, Peter; Salier Eriksson, Jane; Rosdahl, Hans (Frontiers in Sports and Active Living, 2020)
Background: Knowledge about exercise intensity and energy expenditure combined with trip frequency and duration is necessary for interpreting the character and potential influencing capacity of habitual cycle commuting on e.g., health outcomes. It needs to be investigated with validated methods, which is the purpose of this study. Methods: Ten male and 10 female middle-aged habitual commuter cyclists were studied at rest and with maximal exercise tests on a cycle ergometer and a treadmill in the laboratory. During their normal commute in the Stockholm County, Sweden, their oxygen uptake, heart rate, energy expenditure, ventilation, blood lactate, rated perceived exertion, number of stops, durations, route distances and cycling velocities were monitored with validated methods. The frequency of trips was self-reported. Results: The relative exercise intensity was 65% of maximal oxygen uptake, and the energy expenditure was 0.46 kcal per km and kg body weight for both sexes. Sex differences in MET-values (men, 8.7; women 7.4) mirrored higher levels of cycling speed (20%), body weight (29%), oxygen uptake (54%) and ventilation (51%) in men compared to women. The number of METhours per week during peak cycling season averaged 40 for the men and 28 for the women. It corresponded to a total energy expenditure of about 3,500 and 1,880 kcal for men and women, respectively. The number of trips per year was about 370, and the annual distance cycled was on average 3,500 km for men and 2,300 for women. Conclusion: Cycle commuting is characterized by equal relative aerobic intensity levels and energy requirements for a given distance cycled by men and women. Based on an overall evaluation, it represents a lower range within the vigorous intensity category. The combined levels of oxygen uptake, durations and trip frequencies lead to high levels of METhours and energy expenditure in both men and women during both peak cycling season as well as over the year. Overall, the study presents a novel basis for interpreting cycle commuting in relation to various health outcomes.